Blockchain technologies as a means of sale of lease right on the agricultural lands - Buiak, Lesia; Pryshliak, Kateryna; Buiak, Lilia (Herald of Economics, 2023)
Introduction. A prerequisite for the market circulation of agricultural land is the formation of the appropriate infrastructure, an important component of which is land auctions, which have a thousand-year history and are widely used in many countries of the world.The purpose of the article. The purpose of the article is to improve the process of conducting land auctions regarding the sale of lease rights on agricultural land by the procedure of introducing electronic auctions using blockchain technology.Methods. Methods of scientific knowledge, method of analogies, methods of analysis and synthesis, method of system analysis, economic and statistical methods were used to reveal the set goal.Results. The institutional content of the market infrastructure for ensuring the circulation of agricultural land has been improved through the implementation of proposals for the implementation of purchase and sale transactions and land lease rights in the form of an electronic auction, which, unlike the existing one, is complemented by the procedure for introducing electronic auctions using blockchain technology, which allows to increase the speed of transactions, reduce costs and prevent corruption.Perspectives. Further research will be aimed at the introduction of electronic trading using blockchain technology, which allows to increase the speed of transactions, reduce costs and prevent corruption.